International Business as a Possible Civilizing Force in a Cosmopolitan World - Bowie, Norman E. (2019)
The effect of capitalism on the quality of life has been much debated. Albert O. Hirschman has classified the views of the impact of capitalism on the quality of life as civilizing, destructive, and feeble. I believe that multinational corporations (MNCs) should be and could be a civilizing force in today’s cosmopolitan but turbulent world. A number of initiatives will be discussed with special emphasis on business contributions to human rights and to the achievement of past and present United Nations (UN) initiatives. As MNCs undertake these initiatives, they will do well by doing good.
Keywords: UN Global Compact; Sustainable Development Goals (SDGs); multinational corporations (MNCs); Human Rights; Destructive capitalism; Civilizing capitalism